When Death Became Thinkable: Self-Sacrifice in the Women's Social and Political Union. Issue 2 (20th October 2016) - Gullickson, Gay L
Abstract: Hundreds of British suffragettes, members of the Women's Social and Political Union, risked injury and even death as they campaigned for the right to vote in the early twentieth century. This study asks why some women were willing to take such risks and others were not. It focuses on Emmeline Pankhurst, Lady Constance Lytton, and Emily Wilding Davison, the three most famous women who were willing to die for the right to vote. The study argues that the answer to the "why" question lies in the suffragettes's decisions to engage in civil disobedience and go to jail. Denied classification as political prisoners, incarceration introduced them to the general population in women's prisons–poor women and children whose crimes ranged from abortion to theft of food, and who, likely as not, had been abused by men in their lives. These prison encounters, combined with the government's decision to forcibly feed them if they went on hunger strikes, transformed their pre-existing concern for the poor into an imperative to end discrimination and justice against women. Danger did not deter them; they could not not help. It is one of the ironies of history that the suffragettes sacrificed themselves to make the sacrifice of women unnecessary.